2019
DOI: 10.1002/btpr.2805
|View full text |Cite
|
Sign up to set email alerts
|

Identification of upstream culture conditions and harvest time parameters that affect host cell protein clearance

Abstract: During early stage bioprocess development, characterizing interactions between unit operations is a key challenge. Such interactions include the release of host cell enzymes early in the process causing losses in product quality downstream.Using a CHO-expressed IgG1 system, the impact of cell culture duration was investigated using a 50 L bioreactor and performing scale-down protein A purification. While antibody titer doubled during the last week of culture, the post-protein A host cell protein (HCP) levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…To better assess the performance of a process, upstream and downstream aspects should be considered together (Agarabi et al 2017;Wilson et al 2019). Results showed similar host cell dsDNA and total protein contamination levels, fewer large-sized virus and other aggregates, and significant increase in volumetric virus productivity, when using an acoustic settler in comparison with an ATF system.…”
Section: Introductionmentioning
confidence: 99%
“…To better assess the performance of a process, upstream and downstream aspects should be considered together (Agarabi et al 2017;Wilson et al 2019). Results showed similar host cell dsDNA and total protein contamination levels, fewer large-sized virus and other aggregates, and significant increase in volumetric virus productivity, when using an acoustic settler in comparison with an ATF system.…”
Section: Introductionmentioning
confidence: 99%
“…Here we present a program to monitor parallel bioreactor systems in high-throughput microbial cultivations. With this program, we can supervise if replicates follow a coherent pattern throughout (16,17,18; feed rate: µ set = 40% of µ max ). The DOT profiles of Reactor 16 deviates from its group of replicates, indicating the system stops reacting to the pulse-based feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The technical requirements are already met by modern HT robots with developments at the µL scale. Significant advantages are offered by mini-bioreactors (MBR) with working volumes between 10 and 250 mL [17][18][19], integrated online sensors for pH and DOT, integrated control of pH and substrate feeding [20][21][22] and automated at-line sampling and analysis [8,21,23]. Additionally, computer aided tools that enable advanced process control and feedback operation of the robots and the MBRs have been developed, but are rarely used [17,18,20,22,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to date, only a few published works have linked upstream and downstream studies together. 16,17,20,21 In a previous paper, 22 we have shown that upstream operating conditions, including culture duration, that are optimized for higher levels of antibody expression, can result in decreased product quality. We have shown the effects of culture duration and upstream harvest time on antibody titer, as well as on product monomer levels and the amount of HCPs present in purified material, which highlighted that culture duration should not be extended purely for the purpose of expressing more antibodies.…”
mentioning
confidence: 99%